Rancang Bangun Pengontrolan Eksitasi Generator Menggunakan Remote Control - Vivian R. Siburian; Zulkifli Bahri; Syarifah Muthia Putri (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
Electrical Machinery Laboratory, University of Medan Area is one of the laboratories based on energy conversion, and it requires a large source of electrical energy with a variable voltage (voltage can be set from 0.) The excitation system is a DC power supply system as a reinforcement to an electric generator or generator. as a magnetic field generator, so that a generator can produce electrical energy with a large generator output voltage depending on the magnitude of the excitation current. The excitation voltage required to meet the demand is 82 Volt DC. From the results of the test data obtained by 98.1 Volt DC, this is already sufficient to be able to regulate the variable generator excitation voltage. So that the planning of this tool can make it easier to regulate the excitation of the generator from wherever it is, both from a short distance and long distance without using a cable (wireless) by using the Remote Control.